Entre la ville et la mer, entre la France et le Brésil : penser la balnéarisation - Laurent Vidal; Paulo Cesar da Costa Gomes (Confins)
This article deals with the general framework of the questions and orientations leading to a collective survey bringing together historians and geographers from France and Brazil, about the production process of the seaside area, as well as Atlantic circulation of models, experiences and practices. It is the evolution of the city-sea contact, its constant renegotiations as well as the challenges it imposes that are at the heart of this initiative